Pengaruh dukungan pelayanan kesehatan terhadap pemberian asi eksklusif pada bayi sampai usia 4 bulan di Kota Pekanbaru - Zulfayeni Zulfayeni; Madarina Julia; Siti Helmyati (Jurnal Gizi Klinik Indonesia, 2005)
Background: The prevalence of exclusive breastfeeding until the age of 4 months is low. One of the many factors associated with it is healthcare supports on breastfeeding.